Tolerance of Minorities and Cultural Legitimacy: The Case of Pesantren Khusus Waria Al-Fattah Senin-Kamis Yogyakarta - Safitri, Dian Maya (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2011)
This paper discusses three main ideas; tolerance, pluralism, and cultural legitimacy. By taking Pesantren Khusus Waria Al-Fattah as the illustration, this article proposes an example of how a religious, political, social, and sexual marginalized community can live in harmony with other communities. In this paper, the author believed that pluralism means the legitimacy of all kinds of difference instead of solely seen by the existence of difference itself. Furthermore, this article aims to provide information on the importance of the legitimacy of the culture (cultural legitimacy) which is driven by both elite and community in order to provide equal rights for its citizens, including those who considered as